Modelling Learning in Technical Vocational Education through Power Law: A Study of Textile Garment Machinery Operation - Ismael Yépez, Rolando; Ormaza, Maricela Fernanda (Journal of Technical Education and Training, 2025)
The development of practical competencies in technical and vocational education and training (TVET) has garnered significant interest in recent years, particularly in applying tools for measuring and understanding the learning process. This study aims to model and analyze the learning process of three high-performing students in operating straight stitch sewing machines using Wright's Learning Curve model. A non-experimental quantitative design with a descriptive scope was employed. Data were collected from three high-performing students during their learning process in operating straight stitch sewing machines. Wright's Learning Curve model (1936) was used for analysis, applying a logarithmic transformation to estimate parameters through linear regression. Model validation was performed using the coefficient of determination (R²) and mean absolute percentage error (MAE%). Additionally, standard and total production times for 200 cycles were calculated using integral formulas. The model showed a good fit with determination coefficients between 0.69 and 0.74, and mean percentage errors between 12.97% and 19.74%. The standard times achieved for 200 cycles ranged from 23.23 to 62.13 seconds, with total production times between 79.13 and 211.88 minutes. These indicators provide measurable targets for planning vocational training in garment manufacturing, specifically concerning the operation and use of the sewing machine.